PENERAPAN MEDIA BOARD GAME DALAM MENINGKATKAN KEMAMPUAN MENGHAFAL DOA-DOA PENDEK PADA SANTRI DI MA’HAD MIFTAHUL JANNAH KECAMATAN RAMBUTAN KABUPATEN BANYUASIN - Nevy Nahrisyah; Abu Mansur; Nyimas Yunierti Prihatin (STKIP Subang, 2026)
The background of this study focuses on the students' short prayer memorization skills, which are still not optimal, as students often feel bored and unmotivated due to a learning process that tends to be monotonous and relies solely on memorization books. The purpose of this study was to determine the memorization abilities of students before and after the application of Board Games, as well as to determine whether this medium could improve the ability to memorize short prayers among students at Ma'had Miftahul Jannah. The method used in this study was a quantitative approach with an experimental type (Quasi Experimental) using a One Group Pretest-Posttest design. Data collection techniques included observation, tests (oral), and documentation. The data analysis technique used to test the research hypothesis was the Wilcoxon Signed Ranks Test because the data was not normally distributed. The results showed that there was a significant effect of the Board Game media on improving the students' ability to memorize short prayers. Before the media was implemented, the students' abilities were predominantly in the low category (56%) with an average score of 51.41. After the Board Game media was implemented, the students' memorization abilities improved significantly to the high category with an average score of 90.38. Based on the Wilcoxon test results, a significance value of 0.000 < 0.05 was obtained, which means that the Board Game media is very effective in helping students improve their memorization of short prayers.